Is it funny? A Case Study of Chinese College Students' Humor Appreciation on English Jokes (International Journal of Language, Literacy and Translation, 2025)
As Schmitz (2002) suggested, it would be useful to conduct experiments in different parts of the world focusing on the appreciation of three types of humor, which are universal or reality-based humor, culture-based humor, and linguistic or word-based humor. This paper aims to investigate the understanding of the three types of humor on Chinese native speakers. 159 Chinese college students finished the online survey by judging the funniness of selected 21 English jokes divided evenly into three types. This study proved Schmitz’s proposal that universal jokes are the funniest and cultural jokes are the least funny, which implicated that universal or reality-based humor is easier to be appreciated than the other two types. Moreover, Chinese male college students score higher than female college students in the there types of humor, however, there are no significant differences based on English proficiency, living time abroad, and educational background.